Drilling rig drive parameter identification system - Khilov, V. S.; Dyfort, V. V.; Pavlyshyn, S. V.; Pavlyshyna, O. Yu.; Хілов, В. С.; Дифорт, В. В.; Павлишин, С. В.; Павлишина, О. Ю. (ТОВ «ТЕХНІЧНИЙ УНІВЕРСИТЕТ «МЕТІНВЕСТ ПОЛІТЕХНІКА», 2025)
The purpose of the research is to develop and synthesize an effective system for identifying the parameters of the drilling rig drive, considering the specifics of its dynamic characteristics, to increase the accuracy of modeling, control and diagnostics of the technical condition of the drive. Research methodology. In the research process, a systematic approach was used to synthesize a system for identifying the parameters of the drilling rig drive, which involves a phased analysis of the dynamic characteristics of the control object, the development of an adequate mathematical model, and the implementation of adaptive identification algorithms. Research findings. The following methods of identifying drive parameters were analyzed: the least squares method (LSM), the model method with a reference adaptive mechanism (MRAS), Kalman filters (KF, EKF, UKF), frequency analysis methods, methods based on artificial intelligence (AI). Regarding the selected identification object, it is rational to apply the canonical non-search gradient self-tuning algorithm using an “auxiliary operator”, since it is possible to synthesize the desired algorithm based on integration operations with subsequent significant simplification, which contributes to increasing the speed of the entire system. Originality. The scientific novelty of the research lies in the development and synthesis of a new system for identifying the parameters of the drilling rig drive, which provides increased accuracy and speed using adaptive data processing algorithms and mathematical modeling. Unlike existing approaches, the work first proposes a method for combining real experimental data with an analytical model of the drive to refine dynamic parameters in real time. This allows significantly improving the efficiency of drive control in variable drilling conditions. The practical value of the research lies in the development of an effective system for identifying the parameters of the drilling rig drive, which allows for the accurate determination of variable dynamic characteristics of the drive in real time. The proposed approach provides increased control accuracy, reduced energy consumption, timely detection of deviations in the operation of the equipment and prediction of its technical condition. This contributes to increasing the reliability of drilling operations, reducing the risk of accidents and reducing equipment downtime, which is extremely important for mining and ore enterprises.

Мета дослідження полягає у розробці та синтезі ефективної системи ідентифікації параметрів привода бурового верстата з урахуванням специфіки його динамічних характеристик із метою підвищення точності моделювання, керування та діагностики технічного стану привода. Методика дослідження. У процесі дослідження було використано системний підхід до синтезу системи ідентифікації параметрів привода бурового верстата, що передбачає поетапний аналіз динамічних характеристик об’єкта керування, розробку адекватної математичної моделі та впровадження алгоритмів адаптивної ідентифікації. Результати дослідження. Проаналізовані методи ідентифікації параметрів привода: метод найменших квадратів (МНК), метод моделі з еталонним адаптивним механізмом (MRAS), калманівські фільтри (KF, EKF, UKF), методи частотного аналізу, методи на основі штучного інтелекту (AI). До вибраного об’єкта ідентифікації раціонально застосувати канонічний непошуковий градієнтний алгоритм самоналаштування з використанням «допоміжного оператора», оскільки при цьому можна синтезувати шуканий алгоритм на основі операцій інтегрування з подальшим істотним спрощенням, що сприяє підвищенню швидкодії всієї системи. Наукова новизна дослідження полягає у розробці та синтезі нової системи ідентифікації параметрів привода бурового верстата, яка забезпечує підвищену точність і швидкодію завдяки використанню адаптивних алгоритмів обробки даних та математичного моделювання. На відміну від існуючих підходів, у роботі вперше запропоновано методику поєднання реальних експериментальних даних з аналітичною моделлю привода для уточнення динамічних параметрів у режимі реального часу. Це дає змогу суттєво покращити ефективність керування приводом у змінних умовах буріння. Практична значимість дослідження полягає у розробці ефективної системи ідентифікації параметрів привода бурового верстата, яка надає можливість у реальному часі точно визначати змінні динамічні характеристики привода. Запропонований підхід забезпечує підвищення точності управління, зниження енерговитрат, своєчасне виявлення відхилень у роботі обладнання та прогнозування його технічного стану. Це сприяє підвищенню надійності бурових робіт, зниженню ризиків аварій і скороченню простоїв техніки, що є надзвичайно важливим для підприємств гірничо-рудної галузі.
Принципи побудови систем привода шарошкових бурових верстатів для кар’єрів Криворіжжя
Keywords: electric drive; parameter identification; adaptive control; електричний привод; ідентифікація параметрів; адаптивне керування